Forensic characteristics and genetic analysis of both 27 Y-STRs and 143 Y-SNPs in Eastern Han Chinese population. (September 2019) - Lang, Min; Liu, Hai; Song, Feng; Qiao, Xianhua; Ye, Yi; Ren, He; Li, Jienan; Huang, Jian; Xie, Mingkun; Chen, Shengjie; Song, Mengyuan; Zhang, Youfang; et al.
Highlights: High-resolution phylogeny based Han Chinese data for 27 Y-STRs and 143 Y-SNPs reported. A high-resolution Y-SNP panel with the SNaPshot technology was constructed for Han Chinese population analysis. Genetic differentiations between Northern and Southern Han Chinese observed. Abstract: Y-chromosome short tandem repeat (Y-STR) and Y-chromosome single nucleotide polymorphism (Y-SNP) frequency distributions provide resources for assessment of male population stratification among world-wide populations. Currently, the Y-STR Haplotype Reference Database (YHRD) contains numerous Y-chromosome haplotype profiles from various populations and countries around the world. However, for many of the recently discovered and already phylogenetically mapped Y-SNPs, the population data are scarce. Herein, the typing of 27 Y-STRs (Yfiler Plus) and 143 Y-SNPs (self-designed Y-SNP panel) was performed on 1269 unrelated males from 11 Han Chinese populations. Haplogroup O-M175 was the most predominant haplogroup in our Han Chinese data, ranging from 67.34% (Henan Han) to 93.16% (Guangdong Han). The highest haplogroup diversity (0.967056) was observed in Heilongjiang Han, with a discrimination capacity (DC) value of 0.3723. The number of alleles at single-copy loci varied from 2 for DYS391 (Guangdong Han) to 16 for DYS518 (Henan Han). For the majority of the populations (8/11), both the haplotype diversity and DC values are 1.0000. Furthermore, genetic differentiations were observed between Northern and Southern Han Chinese. These genetic differences were mainly reflected in haplogroup distribution and frequency, and they were confirmed by statistical analysis.